KAMPUNG SEHAT TANGGAP DBD DI KELURAHAN GEDAWANG - Elisa Ulfiana; Intan Nugraheni Hasanah; Endri Astuti; Erna widyastuti (GEMASSIKA: Jurnal Pengabdian Kepada Masyarakat, 2021)
Dengue hemorrhagic fever (DHF) is still a problem of health in both urban and semi-urban areas. DHF disease has been a deadly disease since the year 2013. In the health profile of the city of Semarang 2017 Gedawang area is included in the red zone area with the high number of events DHF. Through the DHF Health Care Village program is expected to increase the knowledge and the role of society in realizing a healthy village DHF response. The method of implementing the program is done by providing counseling and simulation. At the end of this activity resulted in an increase in knowledge and community participation in the realization of a healthy village DHF response and when the evaluation is done already formed a report of the Free Numbers Mosquito Repellent each week pasted on the board in each neighbourhood, routine inspection of the Mosquito Repellent, lavender and lemongrass garden and signing of DHF response Village commitment